TREND FOMO DAN TIKTOK DI KALANGAN MAHASISWA - Yanzhuri, Mhd; Marsa, Yummy Jumiati (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2025)
This study examines the trend of FOMO and Tiktok among university students. It aims to describe how the phenomenon of Fear of Missing Out arises as a result of using Tiktok. This research uses a qualitative approach. The research method applied is descriptive-analytical, with data collected through observation, interviews, and documentation. The findings of this study indicate that the Fear of Missing Out (FOMO) phenomenon is a common psychological condition experienced by students in the digital era, particularly due to the use of Tiktok. FOMO is characterized by a fear of being left out of social trends, which drives students to follow viral content. Tiktok amplifies the FOMO phenomenon through behaviors such as imitating content creators, app addiction, and social comparison. The impacts include anxiety, procrastination, sleep disturbances, and decreased academic focus. The factors driving the FOMO phenomenon include the need for social validation, trend pressure, and Tiktok’s addictive algorithm. Tiktok plays a significant role in shaping the intensity of FOMO among students.Previous studies have focused more on the general impacts of social media, but few have specifically examined the Fear of Missing Out phenomenon caused by Tiktok. With its AI-based algorithm that presents content based on user interests, Tiktok creates a personalized experience that potentially triggers FOMO. Unlike earlier research, this study not only looks at the general effects of social media but specifically explores how Tiktok triggers Fear of Missing Out (FOMO) among university students.